Fernerkundung und Geographie - thematische, methodische und technische Perspektiven - Haefner, Harold (ERDKUNDE, 1987)
Even though remote sensing is accepted as an important tool in geography it is not yet systematically used to its full potentials. But by applying clear concepts and in combination with other methods it could contribute substantially to the solution of actual major problems, be it in resources management, regional planning or environmental protection.Satellite data especially are best suited to monitoring various types of land transformation processes. A short history and the state of the present situation of the development of remote sensing methods are presented and reviewed with reference to its mapping, inventoring, monitoring and forecasting aspects. An integrated concept for the monitoring of land transformation processes by various types of remote sensing data and its correlation with auxiliary data, which hasbeen realized at the Dept. of Geography, University of Zurich, is presented. A short prospective view on forthcoming earth observation systems, expecially by the European Space Agency (ESA), demonstrates that remote sensing will be of even greater impor tance to geography in the immediate future and that it is advisable to become familiarized with these data and methods in order to take the best advantage for its application in geography. In conclusion, remote sensing should be used primarily for monitoring processes by including quantitative elements and measuring changes in their temporal-spatial course. To realize this objective, a solid geometric base becomes mandatory, and the addition of a digital terrain model in hilly terrain advisable. The most promising form of organizing data then is a geometric information system (GIS). The ultimate goal should be the development and continuous utilization of operational systems for a durable but flexible management of our natural resources and the protection of the environment.